A review on role of solar photovoltaic (PV) modules in enhancing sustainable water production capacity of solar distillation units. (15th October 2022) - Sharon, H.; Vivar, M.; Fuentes, M.
Abstract: Sustainable production of potable water is one of the United Nations sustainable development goals set for 2030. Among available renewable energy resources, solar energy is abundantly available in most of the fresh water scarce rural and remote locations. Moreover, solar distillation units and solar photovoltaic (PV) modules have been acknowledged as suitable candidates for addressing rising fresh water and electricity demands in these regions. In recent years, researchers have proposed a number of novel hybrid solar distillation units where the solar PV modules are integrated with solar thermal distillation units in different ways to harvest both electric power and potable water. In this work, a detailed review highlighting the classification, working principle, performance and features of these novel hybrid units have been carried out. In most of these hybrid units, integration is highly beneficial for solar thermal distillation units rather than for PV modules. Direct utilization of PV module as absorber, condenser and reflector in solar stills has few drawbacks. However, indirect utilization like utilizing electric power and waste heat energy recovered from PV module in distillation units has posed significant distillate yield enhancement up to 300.0%. In some cases, the integrated PV module has even generated sufficient power for carrying out essential domestic activities. Integrated PV module's performance has also improved significantly in few studies but the magnitude of improvement has not been disclosed clearly in most of the studies as more focus has been given to distillation units rather than PV modules. However, these novel hybrid configurations have not been fully explored & optimized and their techno-enviro-economic aspects have not yet been disclosed in these available precious literatures and they are still available as a potential research gap. Highlights: Classification of different ways to utilize solar PV modules in water distillation units. Indirect utilization is more beneficial than direct utilization. Maximum 25% of PV power is consumed by distillation units. PV performance and distillate yield enhancement by 10.0% and 300.0%. Features and research gaps in each configurations has been highlighted.